Represencing place: the assembly of a vertical landscape from in-between space - Collier, Mishkah (School of Architecture, Planning and Geomatics, 2018)
This project began with a personal attachment to place. An attachment to the Bo-Kaap as the embedded landscape of my spatial memory and cultural identity. My family holds a deep place attachment to the Bo-Kaap. It's the inscribed space of my forefathers and the only place that they've known as 'home'. Since the abolition of slavery in 1834, my family has come to reside in the Bo-Kaap, an uncovering that was discovered through my research at the beginning of the year. After the abolition of slavery, my grandfather's great grandfather purchased the property on the corner of Castle Street and Maxwell Lane, where his family lived for 3 generations until their home was expropriated under the Slums Area Act in 1934. His great-grandchildren later came to purchase available land towards the top of Longmarket Street, which was not affected by the Slums Area Act. This is where my family continues to live till this day. Having grown up in the Bo-kaap, I've witnessed its constant state of flux and the urban pressures that continue to disrupt its historical urban fabric and social character. This realisation has prompted my interest in the Bo-Kaap as both a physical and social space of past and present contestation.